2017
DOI: 10.5530/jyp.2017.9.65
|View full text |Cite
|
Sign up to set email alerts
|

Cemented Versus Cementless Primary Hip Replacement: Assessment of Leg Length Inequality

Abstract: Objective: Following hip arthroplasty surgeries, leg length inequality (LLI) has been reported to be a leading cause of orthopaedic surgery malpractice claims. Most of them developed lengthening of the limb rather than shortening. Small lengthening (≤10 mm) are usually well tolerated by patients and may go unnoticed. In fact, absolute equalisation of limbs length is difficult to achieve and LLI could be minimised but not be avoided. Therefore, this cross-sectional study analysed and compared the LLI between tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…Therefore, pain is an important index that should be considered in postoperative nursing of patients undergoing hip arthroplasty [ 19 ]. Studies have shown that good postoperative analgesia care can shorten the recovery time of patients and reduce the risk of postoperative complications [ 20 ]. The painless management system has been applied well in many departments.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, pain is an important index that should be considered in postoperative nursing of patients undergoing hip arthroplasty [ 19 ]. Studies have shown that good postoperative analgesia care can shorten the recovery time of patients and reduce the risk of postoperative complications [ 20 ]. The painless management system has been applied well in many departments.…”
Section: Discussionmentioning
confidence: 99%
“…Total knee replacement (TKR) and total hip replacement (THR) are highly successful operations for controlling pain, restoring function, and enhancing quality of life for patients with hip and knee osteoarthritis. [1][2][3] They are amongst the most common surgical procedures worldwide. 4 However, approaches to rehabilitation following surgery vary greatly and evidence is limited with regard to successful interventions.…”
Section: Introductionmentioning
confidence: 99%